Monitoring the pH and temperature of IoT-based fish farming using Arduino - Kusdarnowo Hantoro (Jurnal CoreIT: Jurnal Hasil Penelitian Ilmu Komputer dan Teknologi Informasi, 2023)
The Internet of Things (IoT) based intelligent Fish farming refers to the integration of various IoT devices and sensors into traditional fish farming practices to monitor and optimize various aspects of the fish farming environment such as water temperature, pH levels, oxygen levels, and feed schedules. This can help to improve the overall health and wellbeing of the fish, reduce waste, and increase productivity and efficiency. IoT devices can also be used to track the growth and health of individual fish, allowing farmers to make data-driven decisions about when to harvest or move fish to different tanks. The use of IoT technology can also help to detect potential health issues or environmental problems early on, allowing farmers to take preventative measures to minimize the impact on their fish. Overall, smart fish farming using IoT has the potential to revolutionize the way fish are farmed, making the process more sustainable, efficient, and profitable. The project focuses on an IoT-enabled smart fish farming system. In order to deal with them, the system is coupled with an irrigation system. Indonesia’s weather is erratic. This system's microcontroller is an Arduino ESP32. The temperature sensor DSb18B20 and the soil moisture sensor DF Robot are used to regulate the environment. Both a computer and a smartphone are used to display the results.